2019
DOI: 10.1186/s13000-019-0804-6
|View full text |Cite
|
Sign up to set email alerts
|

Rare myeloid sarcoma with KMT2A (MLL)-ELL fusion presenting as a vaginal wall mass

Abstract: Backgroud Myeloid sarcoma (MS) is a rare neoplasm of immature myeloid precursors that form tumor mass outside the bone marrow. The diagnosis of de novo MS can be challenging, particularly in patients with no prior history of hematologic malignancies or when MS involves unusual anatomic sites. Case presentation The patient was a 53-year-old woman with a history of uterine fibroids and vaginal bleeding for many years who presented with a vaginal wall mass. The tumor had h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…NGS demonstrated FLT3 mutation, but no medical literature was found that associates these two neoplasms. The findings in our case may suggest genomic links between MS and HS 11 …”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…NGS demonstrated FLT3 mutation, but no medical literature was found that associates these two neoplasms. The findings in our case may suggest genomic links between MS and HS 11 …”
Section: Discussionsupporting
confidence: 57%
“…Bao et al highlight the importance of KMT2A mutations and rearrangements found in MS with HS‐like morphology, leading us to consider the relationship that these two neoplasms may have in addition to their common oncogenic pathway. We have so far found no literature describing the possibility of transdifferentiation from HS to MS 11 . We ruled out myeloid sarcoma among other entities due to our histological and immunohistochemical findings.…”
Section: Discussionmentioning
confidence: 95%
“…NGS demonstrated FLT3 mutation, but no medical literature was found that associates these two neoplasms. The ndings in our case may suggest genomic links between MS and HS [11].…”
Section: Discussionsupporting
confidence: 55%
“…Mutation of this gene is found in 5%-10% of adult acute myeloid and lymphocytic leukemias; such cases are characterized by poor prognosis and refractory to treatment [14]. Bao et al [11] highlight the importance of KMT2A mutations and rearrangements found in MS with HS-like morphology, leading us to consider the relationship that these two neoplasms may have in addition to their common oncogenic pathway. We have so far found no literature describing the possibility of transdifferentiation from HS to MS [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation